RURAL CERAMIC WORKSHOPS IN ROMAN THRACE : (Second half of the 1st – end of the 3rd century) - Harizanov, Alexander (Rei Cretariae Romanae Fautorum Acta, 2022)
This contribution explores the archaeological evidence for local ceramic production in the province of Thrace during the Principate. Until now, fourteen sites, including villae, villages and presumed artisanal establishments, have provided secure data for the development of this craft. Five ceramic workshops were founded in the last decades of the 1st and the first half of the 2nd century. From the last quarter of the 2nd and until the mid-3rd century the total number of the potteries became twelve. After the Gothic invasions in ca. AD 248-251 there was a noticeable reduction in the number of known ateliers. Only two new sites were established during the second half of the 3rd century, while no more than five of the previous twelve remained operational. The majority of the rural workshops in Thrace was involved in the production of tableware, kitchenware and ceramic building material. Manufacture of flat-bottomed amphorae, oil lamps and terracotta figurines is less frequently documented. Most of the rural kiln sites were probably in operation only through the warm time of the year, given that only three have produced data for installations, which could have enabled the year-round production activities.